Teachers educating to free women's based misconceptions - Montenegro, Marcela (Revista Ensayos Pedagógicos, 2009)
It has not always been easy to be a woman. Throughout history, women have been struggling to have a place in society and to be respected despite of different sacrifices and humiliations that they have had to face in their lives.As a matter of fact, in spite of living under specific rules or customs imposed by society, women have fought to raise their voices and make their rights known through courage, faith, and optimism. Hence, they could be accepted without any judgments and be part of society without any discrimination.